Light-controlled versatile manipulation of liquid metal droplets: a gateway to future liquid robots. Issue 11 (3rd August 2021) - Ren, Hongtai; Jin, Hu; Shu, Jian; Xie, Jie; Wang, Erlong; Ge, Du-An; Tang, Shi-Yang; Li, Xiangpeng; Li, Weihua; Zhang, Shiwu
Abstract : A light-controlled method for the versatile manipulation of liquid metal droplets is introduced. This approach shows the ability of inducing concurrent motion of multiple liquid metal droplets using infrared light without complex and bulky systems. Abstract : The controlled actuation of liquid metal (LM) droplets has recently shown great potential in developing smart actuating systems for applications in robotics. However, there is a lack of a simple approach for the precise manipulation of multiple LM droplets in a 2D plane, which hinders the development of complex control over droplets for realizing useful robotic applications. To overcome this challenge, here, a versatile and powerful light-induced manipulation of LM droplets is presented. The key principle is to selectively activate phototransistors in an electrolyte using infrared laser beams to electrically control LM droplets via Marangoni forces. This approach shows the ability of inducing concurrent motion, splitting, and merging of multiple LM droplets simply using light without complex and bulky systems. Parameters affecting the manipulation of LM droplets are thoroughly investigated. Moreover, a vehicle carrier driven by wheels composed of multiple LM droplets for making a light-controlled relay is demonstrated. We believe such a light-induced control method for manipulating LM droplets has the potential for advancing the development of future field-programmable robotics and droplet-based soft collaborative robots.